The Role of NMDA Receptors in the Effect of Purinergic P2X7 Receptor on Spontaneous Seizure Activity in WAG/Rij Rats With Genetic Absence Epilepsy - Doǧan, Elif; Aygün, Hatice; Arslan, Gökhan; Rzayev, Emil; Avcı, Bahattin; Ayyıldız, Mustafa; Ağar, Erdal (Frontiers in Neuroscience, 2020)
P2X7 receptors (P2X7Rs) are ATP sensitive cation channels and have been shown to be effective in various epilepsy models. Absence epilepsy is a type of idiopathic, generalized, non-convulsive epilepsy. Limited data exist on the role of P2X7Rs and no data has been reported regarding the interaction between P2X7Rs and glutamate receptor NMDA in absence epilepsy. Thus, this study was designed to investigate the role of P2X7 and NMDA receptors and their possible interaction in WAG/Rij rats with absence epilepsy. Permanent cannula and electrodes were placed on the skulls of the animals. After the healing period of the electrode and cannula implantation, ECoG recordings were obtained during 180 min before and after drug injections. P2X7R agonist BzATP, at doses of 50 μg and 100 μg (intracerebroventricular; i.c.v.) and antagonist A-438079, at doses of 20 μg and 40 μg (i.c.v.) were administered alone or prior to memantine (5 mg/kg, intraperitoneal; i.p.) injection. The total number (in every 20 min), the mean duration, and the amplitude of spike-wave discharges (SWDs) were calculated and compared. Rats were decapitated and the right and left hemisphere, cerebellum, and brainstem were separated for the measurements of the advanced oxidation protein product (AOPP), malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), catalase (CAT), glutathione peroxide (GPx), and glutathione reductase (GR). BzATP and A-438079 did not alter measured SWDs parameters, whereas memantine reduced them, which is considered anticonvulsant. BzATP did not alter the anticonvulsant effect of memantine, while A-438079 decreased the effect of memantine. Administration of BzATP increased the levels of SOD and GR in cerebrum hemispheres. A-438079 did not alter any of the biochemical parameters. Memantine reduced the levels of MDA, GSH, and GR while increased the level of CAT in the cerebrum. Administration of BzATP before memantine abolished the effect of memantine on MDA levels. The evidence from this study suggests that P2X7Rs does not directly play a role in the formation of absence seizures. P2X7Rs agonist, reduced the antioxidant activity of memantine whereas agonist of P2X7Rs reduced the anticonvulsant action of memantine, suggesting a partial interaction between P2X7 and NMDA receptors in absence epilepsy model.